2012
DOI: 10.1002/hep.25955
|View full text |Cite
|
Sign up to set email alerts
|

Short-term feedback regulation of bile salt uptake by bile salts in rodent liver

Abstract: The sodium taurocholate cotransporting polypeptide (Ntcp) is the major bile salt uptake transporter at the sinusoidal membrane of hepatocytes. Short-term feedback regulation of Ntcp by primary bile salts has not yet been investigated in vivo. Subcellular localization of Ntcp was analyzed in Ntcp-transfected HepG2-cells by flow cytometry and in immunofluorescence images from tissue sections by a new automated image analysis method. Net bile salt uptake was investigated in perfused rat liver by a pulse chase tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…It was suggested that choleretic and cholestatic effects may involve different PKC isoforms; however, the picture is not entirely consistent. The toxic bile acid TCDC inhibits bile salt transport across the sinusoidal mem- brane by PKC-and PP2B-mediated retrieval of Ntcp from the plasma membrane (33). Phorbol ester-induced endocytosis of Ntcp was shown to be mediated in part by Ca 2ϩ -dependent PKCs (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that choleretic and cholestatic effects may involve different PKC isoforms; however, the picture is not entirely consistent. The toxic bile acid TCDC inhibits bile salt transport across the sinusoidal mem- brane by PKC-and PP2B-mediated retrieval of Ntcp from the plasma membrane (33). Phorbol ester-induced endocytosis of Ntcp was shown to be mediated in part by Ca 2ϩ -dependent PKCs (56).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that the cholestatic bile salt taurolithocholate inhibits hepatic TC uptake and decreases plasma membrane levels of Ntcp (32). Also, taurochenodeoxycholate (TCDC) inhibits TC uptake at the sinusoidal membrane in a chelerythrine-and cypermethrin-dependent way (33). Ntcp is a serine/threonine phosphorylated protein (34) and underlies complex regulation (35).…”
mentioning
confidence: 99%
“…Post-translational short-term regulations of plasma membrane transporters adapt transporter activities according to physiologic demands (Zhang et al, 2008;Kock et al, 2010;Vina-Vilaseca et al, 2011;Gorboulev et al, 2012;Leto and Saltiel, 2012;Mühlfeld et al, 2012;Zhang et al, 2013). Physiologically important examples are insulin-induced recruitment of glucose transporter 4 (GLUT4) to the plasma membrane of adipocytes (Leto and Saltiel, 2012), protein kinase C-dependent endocytosis of organic anion transporter 1 (OAT1) (Zhang et al, 2008(Zhang et al, , 2013, and glucose-induced incorporation of the Na 1 -D-glucose cotransporter SGLT1 into brush-border membranes (BBMs) of small intestinal enterocytes (Gorboulev et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These includes Myrcludex-B [43], Cyclosporin A (CsA), progesterone, propranolol and bosentan [73]. NTCP substrates, such as taurocholate, tauroursodeoxycholate and bromosulfophthalein, also inhibited HBV infection [43,49,73].…”
Section: Sodium Taurocholate Cotransporting Polypeptide (Ntcp)mentioning
confidence: 99%